Evaluation of P5 Implementation in Supporting STEM-based Learning at Vocational Schools using the CIPP Model - Nengka Putri; Remon Lapisa; Ambiyar Ambiyar; Arwizet Arwizet K (Jurnal Penelitian Pendidikan IPA, 2025)
This article evaluates the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMK Negeri 1 Suliki within the framework of the Kurikulum Merdeka. The study aims to assess the alignment of P5 execution with official educational guidelines and identify challenges in its implementation. Utilizing a descriptive qualitative method, data were collected through interviews, observations, and documentation from 158 students and key stakeholders, applying the CIPP evaluation model (Context, Input, Process, Product). The findings reveal a strong alignment between P5 objectives and the school’s vision, yet highlight significant challenges, including limited teacher understanding, inadequate resources, and inconsistent student engagement. The study also highlights the role of P5 activities in fostering competencies related to STEM-based learning approaches, crucial for preparing vocational students for 21st-century challenges. Recommendations for improvement include enhanced educator training, resource allocation, and fostering a supportive school culture. This evaluation provides a comprehensive overview of P5 implementation, contributing to the ongoing discourse on educational quality in vocational schools.